Drosophila CBP is a co-activator of cubitus interruptus in hedgehog signalling. - Akimaru, H.; Chen, Y.; Dai, P.; Hou, D.X.; Nonaka, M.; Smolik, S.M.; Armstrong, S.; Goodman, R.H.; Ishii, S. (Nature, 1997)
The transcription factor CBP, originally identified as a coactivator for CREB, enhances transcription mediated by many other transcription factors. Mutations in the human CBP gene are associated with Rubinstein-Taybi syndrome, a haploinsufficiency disorder characterized by abnormal pattern formation, but the mechanism by which decreased CBP levels affect pattern formation is unclear. The hedgehog (hh) signalling pathway is an important determinant of pattern formation. cubitus interruptus (ci), a component in hh signalling, encodes a transcription factor homologous to the Gli family of proteins and is required for induction of the hh-dependent expression of patched (ptc), decapentaplegic (dpp) and wingless (wg). Haploinsufficiency for the ci-related transcription factor Gli3 causes phenotypic changes in mice (known as 'extra-toes) and humans (Greig's cephalopolysyndactyly syndrome) that have similarities to Rubinstein-Taybi syndrome. Here we show that Drosophila CBP (dCBP) functions as a coactivator of Ci, suggesting that the dCBP-Ci interaction may shed light on the contribution of CBP to pattern formation in mammals.